Empowering Traditional Leaders for Sustainable Peace-building in Bekwarra LGA of Cross River State, Nigeria - Okoli, Omang Theresa; Oyebode , Musibau Olabamiji; Asala, Thomas Bayo (Kashere Journal of Politics and International Relations, 2024)
This study examined the critical role of traditional leaders in fostering sustainable peace in Bekwarra Local Government Area (LGA) of Northern Cross River State, Nigeria. Recognising the unique position and influence these leaders hold within their communities, the research aims to understand how their empowerment can contribute to long-term peacebuilding efforts in a local government characterised by communal conflicts. Through a mixed-methods approach, combining qualitative interviews with community leaders and stakeholders and quantitative surveys of local residents, the study identifies the mechanisms through which traditional leaders can effectively mediate conflicts, mobilise community resources for peace, and facilitate dialogue among conflicting parties. The findings highlight the importance of incorporating indigenous knowledge systems and leadership structures into formal peacebuilding processes. Additionally, the research underscores the need for capacity building and support for traditional leaders to enhance their conflict resolution skills, legitimacy, and ability to collaborate with governmental and non-governmental organisations in peace initiatives. By situating traditional leaders at the heart of peacebuilding strategies, this study contributes to a growing body of literature advocating for a more localised and culturally sensitive approach to conflict resolution and peace maintenance. The implications of this research are significant, suggesting that empowering traditional leaders can lead to more resilient and peaceful communities, not only in Bekwarra LGA but also in other conflict-prone areas of Nigeria and beyond.